Mak mutants of yeast: mapping and characterization. - Wickner, R B (1979)
Killer strains of Saccharomyces cerevisiae are those carrying a 1.5 x 10(6)-dalton double-stranded (ds) ribonucleic acid (RNA) (M) in virus-like particles and secreting a protein toxin. Most yeast (koller or not) also carry a 3 x 10(6)-dalton dsRNA (L). We have mapped mutations in eight of the chromosomal genes needed for maintaining M (mak genes). The mak genes are widely distributed on the yeast map, with no multigene complexes. We show that mutants defective in these and other mak genes lose M dsRNA, but not L dsRNA. The mak3-1 mutation results in markedly decreased cellular levels of L dsRNA, but mak3-1 stains do not lose L dsRNA completely. Mutation of mak16 results in temperature-sensitive growth, whereas mutations in mak13, mak15, mak17, mak20, mak22, and mak27 result in slow growth at any temperature. No effect of mak mutations on mating, meiosis, sporulation, germination, homothallism, or ultraviolet sensitivity has been found. The specificity of mak mutations is discussed.